Author Correction: Variability of crossing phase in older people with Parkinson’s disease is dependent of obstacle height (Scientific Reports, (2018) - Simieli, Lucas [UNESP]; Barbieri, Fabio Augusto [UNESP]; Orcioli-Silva, Diego [UNESP]; Lirani-Silva, Ellen [UNESP]; Beretta, Victor Spiandor [UNESP]; Santos, Paulo Cezar Rocha dos [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (Springer Nature, 2019)
This Article contains errors. Figure Legends 2 and 3 were published as Figure Legends 3 and 2, the correct Figure Legends appear below: Figure 2: Group*obstacle variability for horizontal and vertical foot-obstacle distance before and after obstacle avoidance for leading and trailing limb. (a) Difference between low and high obstacle avoidance; (b) Difference between intermediate and high obstacle avoidance; (c) difference between low and intermediate obstacle. *Difference between people with PD and control group. Figure 3: Variability of kinects parameters for each group in each condition. Additionally, in the Acknowledgements section: “The author thanks to FAPESP #2014/20549-0 - Fundação de Amparo à Pesquisa do Estado de São Paulo.” should read: “The author thanks to FAPESP #2013/21841-3 - Fundação de Amparo à Pesquisa do Estado de São Paulo”.